Knowledge and Disposal Practices of E-Waste Among Polytechnic Engineering Students in Malaysia - Shaarani, Zarina Syuhaida binti (Tropical Scientific Journal, 2026)
Objective: This study examines knowledge and disposal practices of electronic waste (e-waste) among diploma-level engineering students in Malaysian polytechnics. Research Method: Data were collected via an online Google Form from three polytechnics which are Politeknik Tuanku Sultanah Bahiyah (PTSB), Politeknik Seberang Perai (PSP), and Politeknik Sultan Abdul Halim Mu’adzam Shah (POLIMAS). A total of 182 valid responses were obtained, with the instrument demonstrating excellent reliability (Cronbach’s α = 0.98). Findings: The results indicate that most students were able to define e-waste (83.5%) and recognise its health risks (83.0%), but fewer understood its chemical hazards (38.5%). For disposal behaviour, students showed the highest tendency to send damaged electronics to authorised collection centres (M = 3.54, SD = 1.25), yet unsafe practices such as discarding small items into general trash remained common (M = 3.30, SD = 1.33). A clear gradient was observed where students with higher knowledge demonstrated safer disposal practices. Originality: While most studies on e-waste awareness have focused on university students, research involving polytechnic learners remains very limited. Polytechnic engineering students represent a more hands-on and technically oriented group, whose practical training may shape their disposal habits differently. By highlighting this underexplored population, the study contributes new evidence on how future technicians and engineers in Malaysia understand and manage e-waste, offering a more applied perspective to environmental education research